Self and Relative Effects of Competitive State Anxiety on Per-ceived Performance in Middle and High School Taekwondo Ath-letes: An Actor and Partner Interdependence Model Analysis - Hyunwoo Kang; Seyong Jang (Tehran University of Medical Sciences, 2021)
Abstract Background: The present study aimed to provide an empirical theoretical basis for the psychological phenomena that occur among competing athletes. To this end, we utilized the actor and partner interdependence model (APIM) to analyze the self- and relative effects of competitive state anxiety on perceived performance in middle and high school Taekwondo athletes. Methods: Data were analyzed for 372 middle and high school athletes (red group=186, blue group=186) who participated in the first round of the 2020 Korea Taekwondo Association National Taekwondo Competition. Analysis based on the APIM was applied to the collected data, and a path analysis was conducted to verify the self- and relative effects of competitive state anxiety on perceived performance. Results: Cognitive (red: P<0.01, blue: P<0.001) and physical state anxiety (red: P<0.01, blue: P<0.01) exerted a significant negative self-effect on perceived performance in both groups. In contrast, state confidence (red: P<0.001, blue: P<0.001) exerted a significant positive self-effect on perceived performance. Furthermore, cognitive (red: P<0.001, blue: P<0.01) and physical state anxiety (red: P<0.001, blue: P<0.001) exerted a significant positive relative effect on the opponent's perceived performance in both groups, while state confidence (red: P<0.01, blue: P<0.001) exerted a significant negative relative effect on the opponent's perceived performance. Conclusion: Sports psychologists should focus on developing a psychological training program that provides practical psychological support as well as self-regulatory and relative strategies for improving athletic performance in competitive scenarios.